Physiological classification of forest seeds for desiccation and storage tolerance - Oliveira Moraes, Keilyson Naazio; Oliveira, Fiama Natacha Lima de; Bento, Marilene de Campos; Mesquita, Antonio Gilson Gomes; Brito, Rychaellen Silva de (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2020)
The objective of this study was to classify the seeds of aguano (Swietenia macrophylla King) and matamatá (Eschweilera juruensis R. Knuth) according to the desiccation tolerance by the SCR method (Seed Coat Ratio), test of 100 seeds, and by the conventional protocol. The experiment was carried out at the Forest Seed Analysis Laboratory of the Federal University of Acre. For conducting the experiments using the SCR method, 40 seeds dissected in wrap and embryonic axis were used. For the test of 100 seeds, two environments were used, dry control and wet control. For the conventional method, the seeds of S. macrophylla were subjected to drying at 6 and 5% and E. juruensis to drying at 12 and 5%, both species stored for 90 days with 5% of moisture content. The emergency test was used to assess vigor. The SCR method for the seeds of S. macrophylla was P = 0.0046, classified as orthodox and the seeds of E. juruensis classified as recalcitrant with P = 0.96. In the 100 seeds test, 15% drying caused 76% germination for S. macrophylla and the loss of vigor of E. juruensis seeds after drying. When submitted to drying at 5% and stored for 90 days, the seeds of S. macrophylla showed an emergence of 93%, whereas the seeds of E. juruensis did not maintain vigor. The physiological classification of forest species according to desiccation and storage tolerance for Swietenia macrophylla classified as orthodox and Eschweilera juruensis as recalcitrant.